Characterizing ultrashort pulses with photon energies above 1.12 eV based on transient absorption in silicon thin films - Mayank Kumar; Saadat Mokhtari; Tristan Guay; Adrien Leblanc; Kosta Oubrerie; Sohail A Jalil; Elissa Haddad; Gaëtan Jargot; Philippe Lassonde; Heide Ibrahim; Giulio Vampa; François Légaré (JPhys Photonics)
Frequency-resolved optical switching (FROSt) is a phase-matching-free characterization technique for ultrashort pulses based on transient absorption in semiconductors. So far, this technique has been limited to characterizing pulses with photon energies smaller than the bandgap of the semiconductors used. In this work, we extend the method to characterize pulses of photon energy greater than the bandgap of the semiconductor used for characterization. We demonstrate this by characterizing ultrashort visible pulses and supercontinuum using silicon (Si) thin films deposited on a sapphire substrate. We also demonstrate that visible light sources up to a repetition rate of 250 kHz can be characterized using these samples. Therefore, this study highlights the potential of FROSt as a suitable technique for the temporal characterization of weak visible to infrared pulses, including high harmonics generated in solids.